Biofouling and its effects in sensor mounted moored observatory system in Northern Indian Ocean. (January 2017) - Venkatesan, R.; Senthilkumar, P.; Vedachalam, N.; Murugesh, P.
Abstract: Biofouling formation is one of the critical factors which affect the measurement of continuous real time data in offshore moored data buoy sensors. In order to understand the biofouling trend at different water depths, observations were conducted in instrumented data buoy system moored in the coastal waters and in the Northern Indian Ocean in water depths ranging from 2000 to 4500 m. It is identified that biofouling is predominant only up to a depth of 50 m and Lepas anatifera goose neck barnacle is the common biofoulant irrespective of location and water conductivity. The study also presents typical cases of conductivity sensors drifts due to biofouling and preventing techniques adopted for increasing the maintenance interval and to obtain quality data. The results shall serve as inputs for the design and maintenance of offshore facilities and instrumented moored data buoy systems. Highlights: Experiments conduced on deep ocean moored data buoys in Northern Indian Ocean. Biofouling found to be predominant up to 50 m water depths. Lepas antifera goose neck barnacle found to be common bio-foulant. Impact on the reliable performance of oceanographic sensors presented.